2022
DOI: 10.3389/fimmu.2022.862503
|View full text |Cite
|
Sign up to set email alerts
|

Propionic Acid, Induced in Gut by an Inulin Diet, Suppresses Inflammation and Ameliorates Liver Ischemia and Reperfusion Injury in Mice

Abstract: Liver ischemia and reperfusion injury (IRI) is one of the obstacles in liver surgery such as liver resection and transplantation. In this study, we investigated the preventive effect on mouse liver IRI by feeding mice with inulin, which is a heterogeneous blend of indigestible fructose polymer. Mice were fed either a control ordinary diet (CD) or an inulin diet (ID) containing 5% inulin in the CD, for 14 days before the ischemia and reperfusion (IR) maneuver. IR induced-liver damages were significantly amelior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Besides, succinic acid, kojic acid, and propionic acid were highly abundant in the pasteurized PKP–L. reuteri, which are reported to possess a variety of pharmacological effects, including cardioprotective, anti-inflammatory, and antibacterial. , Recent studies highlighted the beneficial impacts of propionic acid on ameliorating liver dysfunctions via activation of the APN-AMPK-PPARα signaling pathway, thereby inhibiting fatty acid de novo synthesis and promoting β-oxidation. Zhou et al found that phenyllactic acid derived from Lactobacillus effectively regulated microbiota composition, improved SCFA production, and reduced inflammatory responses. In addition, the important roles of indole derivatives, indole-3-carbinol, and indole-lactic acid predominately produced by L.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, succinic acid, kojic acid, and propionic acid were highly abundant in the pasteurized PKP–L. reuteri, which are reported to possess a variety of pharmacological effects, including cardioprotective, anti-inflammatory, and antibacterial. , Recent studies highlighted the beneficial impacts of propionic acid on ameliorating liver dysfunctions via activation of the APN-AMPK-PPARα signaling pathway, thereby inhibiting fatty acid de novo synthesis and promoting β-oxidation. Zhou et al found that phenyllactic acid derived from Lactobacillus effectively regulated microbiota composition, improved SCFA production, and reduced inflammatory responses. In addition, the important roles of indole derivatives, indole-3-carbinol, and indole-lactic acid predominately produced by L.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the tested drug compounds in this study on SCFAs production was variable and mostly independent of their effect on bacterial growth, in contrast to earlier studies’ results that a change in abundance of gut bacteria owing to drug usage was correlated to a similar effect on SCFAs production ( Hojo et al., 2018 ). Notably, numerous studies reveal that Bacteroidetes are the main producers of propionate in the human gut ( Salonen et al., 2014 ; Aguirre et al., 2016 ) and this SCFA is known for its ability to suppress inflammation and the increase in its level is associated with cognitive decline in elderly ( Kawasoe et al., 2022 ; Neuffer et al., 2022 ) while low level of propionic acid and acetate was linked to autism( Tetel et al., 2018 ). Progesterone and L-thryoxine reduced the production of propionic acid by B. fragilis .…”
Section: Discussionmentioning
confidence: 99%
“…420 ) was found to alleviate S100-induced experimental autoimmune hepatitis (EAH) by modulating RIP3 signaling of hepatic macrophages ( Zhang et al, 2020 ). In addition, an inulin diet was shown to ameliorate IR-induced ALI, accompanied by significant increases in the abundance of Bacteroides acidifaciens in feces and its SCFAs, especially propionic acid (PA), in the portal vein ( Kawasoe et al, 2022 ). Furthermore, PA alone was sufficient to inhibit macrophages activated through HMGB-1/TLR4 signaling in vitro ( Kawasoe et al, 2022 ).…”
Section: Hepatic Macrophages As Microbial Regulating Targets In Infla...mentioning
confidence: 99%
“…In addition, an inulin diet was shown to ameliorate IR-induced ALI, accompanied by significant increases in the abundance of Bacteroides acidifaciens in feces and its SCFAs, especially propionic acid (PA), in the portal vein ( Kawasoe et al, 2022 ). Furthermore, PA alone was sufficient to inhibit macrophages activated through HMGB-1/TLR4 signaling in vitro ( Kawasoe et al, 2022 ). The gut microbiota metabolite 3,4-dihydroxyphenylpropionic acid was shown to play a similar role in IR-induced ALI ( Li R. et al, 2022 ).…”
Section: Hepatic Macrophages As Microbial Regulating Targets In Infla...mentioning
confidence: 99%
See 1 more Smart Citation